Carbon Stock Estimation and Human Disturbance in Selected Urban Un-Conserved Forests in Entoto Mountain Forest, Addis Ababa, Ethiopia - Lemlem Wondwossen Solomon; Noppol Arunrat; Thamarat Phutthai; Worachart Wisawapipat; Sukanya Sereenonchai; Ryusuke Hatano (Diversity)
Urban forests are crucial for biodiversity and climate resilience. This study investigated the impact of human disturbances on carbon (C) stocks in un-conserved forests of Entoto Mountain, Addis Ababa, Ethiopia, focusing on forest structure: important value index (IVI), species diversity (H’), regeneration pattern status, and C storage in aboveground biomass (AGB), belowground biomass (BGB), litter biomass (LB), and soil. Field data were collected from 35 quadrats across two altitudes, and human disturbances were observed, including firewood collection, tree cutting, soil excavation, and road and infrastructure inside the sample plot. Results indicate low species diversity dominated by Eucalyptus globulus Labill and Juniperus procera Hoechst. Ex Endl., with fair regeneration. Higher altitudes showed greater measured C stock (572.62 tC ha−1) than lower altitudes (495.03 tC ha−1), attributed to larger trees. C values in the upper altitude for AGB, BGB, LB, and soil (0–30 cm) were higher than at lower altitudes. The IVI showed a significant positive correlation with C in aboveground biomass, C in belowground biomass, and total C stock, whereas H’ also showed a significant (p < 0.05) positive correlation with the total number of trees. It is concluded that forest structures contribute to the C stock of this area. Given the importance of the un-conserved Entoto Mountain forest, it is recommended to prioritize the conservation of old-growth forest species in the area, as they demonstrate the highest capacity for C accumulation.